2017
DOI: 10.3390/en10050608
|View full text |Cite
|
Sign up to set email alerts
|

A Data-Driven Method for Energy Consumption Prediction and Energy-Efficient Routing of Electric Vehicles in Real-World Conditions

Abstract: Limited driving range remains one of the barriers for widespread adoption of electric vehicles (EVs). To address the problem of range anxiety, this paper presents an energy consumption prediction method for EVs, designed for energy-efficient routing. This data-driven methodology combines real-world measured driving data with geographical and weather data to predict the consumption over any given road in a road network. The driving data are linked to the road network using geographic information system software… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
101
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(103 citation statements)
references
References 37 publications
2
101
0
Order By: Relevance
“…Data-driven methods have shown good accuracy of prediction and straightforwardness for usage. A data-driven energy consumption prediction method for EVs (used for the energy-efficient routing issue) was developed [59]. A feature of the model is that it makes it possible to distinguish between different energy consumption influencing factors (road characteristics, weather, altitude differences, etc.…”
Section: Methods For Parametrization Of Driver Behaviormentioning
confidence: 99%
“…Data-driven methods have shown good accuracy of prediction and straightforwardness for usage. A data-driven energy consumption prediction method for EVs (used for the energy-efficient routing issue) was developed [59]. A feature of the model is that it makes it possible to distinguish between different energy consumption influencing factors (road characteristics, weather, altitude differences, etc.…”
Section: Methods For Parametrization Of Driver Behaviormentioning
confidence: 99%
“…Speed profile depends on the road type, driver behavior, traffic (accidents, recurrent congestions), weather conditions, etc. [115,116]. A large number of parameters make it hard to predict a BEV's energy consumption in different traffic scenarios.…”
Section: Energy Consumptionmentioning
confidence: 99%
“…Results showed that the prediction error of trip energy consumption is within 25%. De Cauwer et al [115] applied a similar MLR model for predicting energy consumption on road segments, suited for BEV routing. The authors used a neural network based on the road-traffic and weather-related features to predict the speed profile of a road segment.…”
Section: Energy Consumptionmentioning
confidence: 99%
“…Nonetheless, the results derived from our Practical Consumption Function are realistic and very close to findings reported in the literature of EV routing. The incorporation of more advanced formulas like ones presented in [53,54] our method can be considered as the next step in our research. In order to provide the necessary background for the use of the Practical Consumption Function, the data for the distance and elevation are derived from the OpenTripPlanner API, which bases its calculations on OpenStreetMap data for the road network and SRTM data for the elevation.…”
Section: Energy Consumption Model and The Incorporation Of Elevationmentioning
confidence: 99%